Insurgent - Book 2 - Roth, Veronica (New York : Katherine Tegen Books, 2012)
As war surges in the dystopian society around her, Divergent Tris Prior must continue trying to save those she loves--and herself--while grappling with haunting questions of grief and forgiveness, identity and loyalty, politics and love.
Sequel to: Divergent.
Keywords: Identity (Psychology) -- Fiction; Family life -- Fiction; Courage -- Fiction; Social classes -- Fiction; Science fiction